ChemInform Abstract: Rh(III)‐Catalyzed Intramolecular Redox‐Neutral Cyclization of Alkenes via C—H Activation. Issue 25 (24th June 2014) - Shi, Zhuangzhi; Boultadakis‐Arapinis, Melissa; Koester, Dennis C.; Glorius, Frank
Abstract leading to a variety of fused multicyclic lactams of biological interest